Implementation of Village-Owned Enterprises within the Grindle Framework - M. Zaenul Muttaqin; Yansen Alberth Reba; Kazi Mohammad Mahbobor Rahman Mahbobor Rahman (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2025)
This study analyzes the implementation of Village-Owned Enterprises (BUMDes) policy in Indonesia using Merilee S. Grindle's analytical framework that distinguishes between policy content and implementation context. Through a systematic literature review methodology, this research examines 8 international studies on community-based enterprises and compares them with Indonesian BUMDes practices. Similar practices in Finnish fishing cooperatives, Mexican community forest enterprises, Chinese rural development and Lao government-business partnerships provide valuable insights. The research shows that Grindle's framework offers a comprehensive analytical tool to understand the complexity of BUMDes implementation, emphasizing the critical role of the implementation context involving local political dynamics and community participation. Key findings indicate that successful community-based enterprises require strong institutional capacity, active community engagement, government support, and effective governance mechanisms. The study concludes that strengthening the implementation context, particularly institutional aspects and community participation, should be prioritized for effective BUMDes development in Indonesia.